ALTERATION OF GROWTH AND FLOWERING OF Cucumissativus L. BY APPLICATION OF SEX STEROIDS in vitro - `A. Kiełkowska; I. Karaś; A. Noga (Journal of Animal and Plant Sciences, 2017)
The effect of selected sex steroidson plant morphology, flowering and sex expression in Cucumissativus cultivarKmicic F1 was investigated. Plants were cultured on the medium with the addition of progesterone, testosterone and estroneat concentrations of 0.1 and 1.0 µM.All tested steroids caused shortening in the main stem over the control, while the number of main stem nodes was similar to the control. Testosterone and progesterone stimulated female flower, decreasing male flower production. Plants cultured on the medium with estronehad shorteststems and the total number of flowers produced was more than four-fold lower compared to the control; however,a shift toward femaleness was observed. Application of the tested sex steroidsin vitroaltered flower morphology. Pollen viability in the anthers of male flowers developed on plants cultured on the media with steroids was decreased, compare to control, suggesting their effect on pollen development.
Keywords: cucumber; morphology; in vitro flowering; sex hormones; steroids; pollen viability